PENGARUH PELATIHAN DUKUNGAN SOSIAL âSUAMI SMARTâ TERHADAP PENURUNAN TINGKAT DISTRES PADA ISTRI DENGAN KEHAMILAN PRANIKAH (SEBUAH PENELITIAN PENDAHULUAN) - , BERTA DEVI ARYANI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Premarital pregnancy could potentially bring a variety of psychological problems, including distress during pregnancy. These conditions affect the risk of maternal and fetal development was conceived. Husband and wife needed the support of premarital pregnancy in an attempt to overcome these psychological problems. The hypothesis of this research is the training of "Suami SMART" (Sensitif, Mendukung, Aktif, Responsif, and Tahu) can increase spouse support, perceived support, and decrease distress level of wife with premarital pregnancy. Using quasi-experimental research design with experimental groups totaling 3 husbands who received training. Measurements using the spouse support scale, perceived support scale, and distress scale. After conducting a quantitative analysis by Wilcoxon signed ranks test, the results of this study indicate that no significant increase in skills support, no significant increase in in the perceived support of wife, and no significant decrease in distress level of wife as indicated by the value of Z 0.000 and p = 0.500. Instrumental support and perceived esteem support largest increase compared to the other aspects, behavior distress largest decrease compared to the other aspects.